ANALISIS DETERMINAN INDEKS PEMBANGUNAN MANUSIA MENGGUNAKAN VARIABEL MAKROEKONOMI (STUDI KASUS 34 PROVINSI DI INDONESIA TAHUN 2019-2021) - Julianti, Shella Marliani; Sukarniati, Lestari (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2022)
The Human Development Index (HDI) should be placed as the first and main priority in development. This is because humans are the basic capital in other developments. This research aims to determine the factors that influence HDI using macroeconomic variables with case studies of 34 provinces in Indonesia. The data used is quantitative data with longitudinal or panel dimensions. The research method implemented is the fixed effect model (FEM). The research results simultaneously show that all independent variables in the model have a simultaneous and significant effect on HDI. Partially, significant variables include early marriage, family expenditure per capita, domestic investment, unemployment and poverty. It is important for future research to use other research methods to complement the literature.